2022
DOI: 10.1590/1980-220x-reeusp-2021-0417
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an educational video in older adults’ perception about falling risks: a randomized clinical trial

Abstract: Objective: to assess the effectiveness of using an educational video in comparison with verbal nursing guidelines in increasing older adults’ perception of falling risks. Method: this is a randomized clinical trial in a cluster, with 138 community older adults, randomized into an intervention group, which watched an educational video, and a control group, which received verbal instructions. The perception of falling risks was assessed by FRAQ-Brazil in the pre-test and after a 30-day follow-up. Student’s t-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
0
4
0
7
Order By: Relevance
“…(10,11,19) O uso dessa ferramenta tem integrado as ações de educação em saúde, educação permanente e o ensino melhorando a aquisição de habilidades e o desempenho prático. (20)(21)(22) Nesse contexto, a validação se propõe a avaliar de forma criteriosa e rigorosa o material a ser desenvolvido, por isso os participantes devem ser expertises na temática investigada. (10) Neste estudo, os juízes foram de diversas regiões brasileiras, o que facilitou uma análise das diferenças culturais do país para melhor compressão do vídeo.…”
Section: Discussionunclassified
“…(10,11,19) O uso dessa ferramenta tem integrado as ações de educação em saúde, educação permanente e o ensino melhorando a aquisição de habilidades e o desempenho prático. (20)(21)(22) Nesse contexto, a validação se propõe a avaliar de forma criteriosa e rigorosa o material a ser desenvolvido, por isso os participantes devem ser expertises na temática investigada. (10) Neste estudo, os juízes foram de diversas regiões brasileiras, o que facilitou uma análise das diferenças culturais do país para melhor compressão do vídeo.…”
Section: Discussionunclassified
“…In spite of no paper in Table 4 satisfy inclusion criterium (iv)empirical results comparing video designs, the studies from Sá et al (2020) and Sá et al (2022) are related, not only each paper has six authors, from which five authors are the same, the second paper is the continuation of the first, that is, it is based on the instructional video produced in the first. The combination of the two papers would be a study that satisfies inclusion criteria (i), (ii), and (iii) (except criteria iv), and it would not be included in any exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…This local scenario from Brazil suggests that first most local publications regarding instructional videos are about constructing and validating videos. Almost all papers present the construction and validation of instructional video, except Sá et al (2022), that is, 12 in 13. However, if the work of Sá et al (2020) and Sá et al (2022) is considered as one, as previously suggested, then, in fact, all papers would be related to constructing and validating educational videos (12 in 12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations